Роль блогерських платформ у стратегіях промоції книжкової продукції - Недошитко, Ірина (Видавництво Львівської політехніки, 2025)
The abstract analyzes the experience of using relevant digital marketing tools such as social networks, blogging platforms which in today's information overload play an important role in attracting the attention of the readership and strengthening the presence of literary content in the media space. The author shows the role of social networks Instagram and YouTube for the development of book blogs, as they provide a wide range of opportunities for interaction with the audience. Among the main motivations for creating book blogs, Ukrainian authors point to the desire to share their own impressions of what they have read, express their personal opinions about works, authors, or publishers, as well as find like-minded people and form a reader community.
Keywords: book blog; social networks; Instagram; YouTube; promotion